Identifying the barriers for the decline of Eye donation among the post-mortem cases in SCBMCH, Cuttack. (Journal of Forensic Medicine & Toxicology, 2025)
Globally blindness is a public health problem. Corneal blindness is the third leading cause of blindness worldwide after cataract and glaucoma. Corneal transplantation is the most frequently performed type of transplant worldwide. Cadaver donors are the only source of donor corneas. The need therefore is to educate the masses about eye donation in an effort to increase the procurement of corneas by eliminating the prevailing misbeliefs and misconceptions. The study was done to identify the hindrances and misconceptions and steps to overcome them. The study was done on 1030 participants who were the next of the kin of the deceased autopsied in the central mortuary of SCB MCH, Cuttack, Odisha. Only about a third of the total study population had heard about corneal donation, and still lesser had some knowledge regarding it. Among the willing, the males outnumbered the females; and the urban population was keener to donate corneas. The Sikh population were more willing than the Hindus and Muslims. Majority of the willing considered corneal donation as noble act. The rural population was more familiar on corneal donation. Print media was the major source of information and least was from news media. Conclusion: Disfigurement was the most common misconception, whereas ignorance was the most common hindrance in corneal donation. Educating the children on organ donation from school level can develop the long-term counselling and constant sensitization benefits when they grow up as an adult.
Keywords: Corneal Blindness; Corneal transplant; Corneal donation; Disfigurement.